Postmortem diagnosis of COVID-19: Antemortem challenges of three cases at the 37 Military Hospital, Accra, Ghana - Seth A. Attoh; Frederick Hobenu; Lawrence Edusei; Kwasi Agyeman-Bediako; Clement T. Laryea; Edward O. Nyarko; Michael K. Amedi; Richard H. Asmah; Edward Asumanu; Mary McAddy; Anthony Maison; Godwin Nyarko; et al. (African Journal of Laboratory Medicine, 2020)
Background: Consistency among clinical symptoms, laboratory results and autopsy findings can be a quality measure in the diagnosis of coronavirus disease 2019 (COVID-19). There have been classic clinical cases that have met the case definition of COVID-19 but real-time reverse-transcription polymerase chain reaction (rRT-PCR) tests of nasopharyngeal swabs were negative.